PATISIRAN PH 2 OPEN-LABEL EXTENSION STUDY IN FAMILIAL AMYLOIDOTIC POLYNEUROPATHY. Issue 12 (15th November 2016) - Schmidt, Hartmut; Adams, David; Coelho, Teresa; Conceicao, Isabel; Waddington-Cruz, Marcia; Buades, Juan; Campistol, Josep; Pouget, Jean; Gollob, Jared; Suhr, Ole
Abstract : Background: Familial Amyloid Polyneuropathy (FAP) is a progressive disease caused by deposition of transthyretin (TTR). Patisiran is an investigational, small interfering RNA (siRNA) inhibiting TTR. This abstract highlights patisiran's long-term safety. Methods: Phase 2 OLE study to evaluate patisiran's safety. Patisiran's effect on serum TTR levels, impact on neuropathy impairment scores and QOL were assessed. Results: 27 patients with FAP enrolled; median age 64 years. Patisiran was generally well tolerated out to 23-months. Five patients experienced SAEs (unrelated) including one discontinuation (gastroesophageal cancer); patient subsequently died. Flushing (25.9%) and infusion-related reactions (18.5%) were mild in severity; no discontinuations resulted. Approximately 80% sustained mean serum TTR lowering resulted with a mean nadir of up to 93% between doses. Among the 20 evaluable patients, neuropathy impairment scores were stable through 18-months; mean change in mNIS+7 and NIS of 1.7 and 4.2 points, respectively. This compares favorably to 17–26 point mNIS+7/NIS increase estimated at 18-months from prior FAP studies. Stabilization of QOL measures and improvement of distal thigh sweat gland nerve fiber density observed. Conclusion: Data demonstrates that 18-months of patisiran administration was generally well tolerated, resulted in sustained mean serum TTR lowering, supporting the hypothesis that TTR knockdown potentially halts neuropathy progression.